2007
DOI: 10.1093/jn/137.3.683
|View full text |Cite
|
Sign up to set email alerts
|

Preschool-Aged Children with Iron Deficiency Anemia Show Altered Affect and Behavior ,

Abstract: This study compared social looking and response to novelty in preschool-aged children (47-68 mo) with or without iron deficiency anemia (IDA). Iron status of the participants from a low-income community in New Delhi, India, was based on venous hemoglobin, mean corpuscular volume, and red cell distribution width. Children's social looking toward adults, affect, and wary or hesitant behavior in response to novelty were assessed in a semistructured paradigm during an in-home play observation. Affect and behavior … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
85
1
3

Year Published

2010
2010
2019
2019

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 111 publications
(91 citation statements)
references
References 52 publications
2
85
1
3
Order By: Relevance
“…Previous studies have revealed that iron was associated with socio-cognitive and socio-emotional development and functioning [46][47][48]. A disorder in this area is one of the core symptoms of ASD.…”
Section: Autism Spectrum Disorder (Asd)mentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have revealed that iron was associated with socio-cognitive and socio-emotional development and functioning [46][47][48]. A disorder in this area is one of the core symptoms of ASD.…”
Section: Autism Spectrum Disorder (Asd)mentioning
confidence: 99%
“…It has been well documented that iron is associated with socioemotional development and that ID may disturb the development of emotional regulation [40,46,47,58], although clinical studies on the association between IDA and BD are few. Our results showed a higher prevalence of BD among IDA subjects.…”
Section: Bipolar Disorder (Bd)mentioning
confidence: 99%
“…While these signs are typical for any anemia, the development of pica is unique to IDA. Evidence of blood loss, such as melena, hematuria, or bleeding from other sites may be noted at the time of physical examination [24][25][26][27][28][29]. …”
Section: Clinical Featuresmentioning
confidence: 99%
“…More specifically, it is estimated that investment in programmes to control anaemia among children, which certainly affects their cognitive abilities, could provide an increase of 13-25 % of the value of their future salaries as adults, improving their chances of survival and social inclusion (3) . Even within a short period (7 months), the assessed training programme promoted significant changes in the health status of the children based on the indicator used, which is important considering the consequences of anaemia in the long term (6,7) . Therefore, the findings evidenced in the present study, in concordance with those of other experiments, reinforce the importance of establishing policies for nutritional education as a strategy for improving child health, even in day-care centres with few resources and diverse demands (3,30) .…”
Section: ·20mentioning
confidence: 99%
“…Furthermore, despite high public investment in health policies worldwide, which subsidises the development and execution of innumerable programmes to control and prevent the most prevalent childhood illnesses, high rates of infection and nutritional disorders are still present among infants and pre-school children in developing countries (5) . Among these conditions, anaemia stands out for its multifactorial detection characteristic and for its potential to cause psychological, behavioural and neurological sequelae that are irreversible and proportional to the duration of this specific nutritional deficiency, the age of onset and its severity (6,7) . Within this context, the objective of the present study was to test the training of day-care educators as a useful tool for reducing the prevalence of anaemia in children, which meets the prerequisites of effectiveness, low cost, straightforward applicability and a significant impact on the improvement of the health and nutrition of children attending public and philanthropic day-care nurseries.…”
mentioning
confidence: 99%